Activation of porous Si blue emission due to preanodization ion implantation - Rozhin, A.G.; Klyui, N.I.; Litovchenko, V.G.; Melnik, V.P.; Romanyuk, B.N.; Piryatinskii, Yu.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Implantation of B⁺, N⁺, and B⁺+N⁺ ions into initial silicon wafers was carried out before anodization process. The results of photoluminescent (PL) study of porous Si samples prepared on B⁺ or N⁺ implanted wafers show a decrease in the photoluminescence intensity when compared with the initial porous Si. In contrast to this, the B⁺+ N⁺ double doped samples show the increasing of the photoluminescence intensity. This effect can be explained by donor-acceptor pairs formation, and, as a result, the new recombination-active radiative channel creation. Rapid thermal annealing (RTA) treatment leads to significant decrease of PL intensity in the longwave spectral range for initial sample and samples prepared on implanted substrates. Furthermore, RTA treatments leads to the activation of the porous Si high-energy PL formed on the B⁺ implanted wafers.